2010
DOI: 10.1158/0008-5472.can-10-1341
|View full text |Cite
|
Sign up to set email alerts
|

Mage-A Cancer/Testis Antigens Inhibit p53 Function by Blocking Its Interaction with Chromatin

Abstract: The p53 tumor suppressor plays a major protective role in tumor prevention by coordinating changes in gene expression that lead to the elimination of cancer cells. Mage-A proteins comprise a family of metastasisassociated transcriptional regulators that potently inhibit p53 function. Here, we show that Mage-A interacts with 3 distinct peptides each of which is located within the DNA binding surface of the core domain of p53 and encompasses amino acids that are critical for site-specific DNA binding. These data… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
121
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(133 citation statements)
references
References 36 publications
5
121
1
Order By: Relevance
“…MDSCs secrete multiple factors that may support the growth and survival of tumor cells (39)(40)(41)(42), and it would be of interest to confirm whether MDSCs secrete soluble factors that regulate MAGE-A4 expression. In further support of this, it has previously been reported that CT antigen expression is association with cell cycle progression and proliferation (43)(44)(45), apoptosis (13) and susceptibility of cancer cells to cytokines (46), suggesting that the CT antigen itself may be associated with prognosis.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…MDSCs secrete multiple factors that may support the growth and survival of tumor cells (39)(40)(41)(42), and it would be of interest to confirm whether MDSCs secrete soluble factors that regulate MAGE-A4 expression. In further support of this, it has previously been reported that CT antigen expression is association with cell cycle progression and proliferation (43)(44)(45), apoptosis (13) and susceptibility of cancer cells to cytokines (46), suggesting that the CT antigen itself may be associated with prognosis.…”
Section: Discussionsupporting
confidence: 64%
“…MDSCs are a heterogeneous group of pathologically activated immature myeloid cells and myeloid precursors that possess potent immunosuppressive activity (10)(11)(12). MDSCs have been identified in the peripheral blood, lymphoid tissue and tumor tissue in a number of experimental mouse models (13). Other studies have also demonstrated that MDSCs inhibit the effector…”
Section: Introductionmentioning
confidence: 99%
“…13 923 melanoma cells have been described. 12 HA-MageA1, -A2, -A4 and -A6 were cloned in pCDNA3 (Invitrogen). GST-MageA2, and GST-MageA4 were obtained by subcloning in pGEX-4T1 (GE Healthcare Biosciences, Buckinghamshire, UK).…”
Section: Methodsmentioning
confidence: 99%
“…10 Subsequently, other groups also described an opposite correlation between MAGE-A gene expression and p53 activity. 7,11,12 Interestingly, only MageA4 has been shown to be involved in some potentially anti-tumor functions such as gankyrin oncoprotein inhibition 13 and apoptosis induction. 14,15 It has been demonstrated that escape to cellular senescence is one of the first barriers to be bypassed during transformation.…”
mentioning
confidence: 99%
“…Recently, it has been shown that MAGEA cancer testis antigens inhibit the function of p53 by blocking its interaction with chromatin. 18 In several cancer types, eg multiple myeloma, bladder cancer, non-small cell lung cancer, hepatocellular carcinoma, breast, colorectal and pancreatic ductal adenocarcinoma, the high expression of cancer testis-X genes is associated with poor differentiation grade, progressive disease and worse prognosis. [19][20][21][22] There are only limited studies on cancer testis antigen expression in testicular germ cell tumors.…”
mentioning
confidence: 99%